Future Directions in Aerospace Technologies - McLean, Donald (Universiti Putra Malaysia Press, 2001)
From an assessment of the estimated needs for civil and military aircraft which arise from the predicted future growth of civil aviation and the known needs of the world's defense forces, it is shown that there are compelling reasons for international and inter-company collaboration to meet the demands. From that evidence and two British reports concerning the future of the UK and European aeronautics industry it has been possible to indicate the technology acquisition strategies proposed for future success. Underpinning these strategies are three categories of technology, namely Foundation Enhancing and Supporting. These categories are discussed before presenting a consideration of appropriate aerospace technologies for the future including the propulsion cycle, the use of double fuselage aircraft, the blended wing body concept, the design of long haul subsonic aircraft, new cockpit technology and air traffic management systems.